NERACA KARBON PRA DAN POST HTI DI BLOK KHUSUS KESATUAN PENGELOLAAN HUTAN TASIK BESAR SERKAP RIAU - Ari Suharto; Dodik Ridho Nurrochmat; Tania June (Graduate School Bogor Agricultural University (SPs IPB), 2017)
Climate change is the current global issue that has been discuss over two decades. In Indonesia context, the total greenhouse gases (GHG) emissions from all sectors including land use change forestry, energy, peat fire, waste, agriculture and industry is 1.377.982,95 Gg CO2e. The GHG emission only counted by three main gases such as CO2, CH4 and N2O. Related to mitigation efforts by private company to reduce these emissions. This study more focus on comparation on how much natural forest can generate CO2 absorpsion from tree growth and how much plantation plantation company generate CO2 absorpsion from tree growth and their emission from its operational activities specially on transportation and N addition by synthentic fertilizer. The study conducted in specific block of forest management unit of Tasik Besar Serkap, Riau Province since January 2016 until June 2016. Based on this study, CO2 absorpsionfrom natural forest is 33.199.866,70 ton CO2, CO2 emissionfrom natural forest is 0, CO2 absorpsion from plantation company 13.366.266,32 ton CO2, CO2 emissionfrom synthetic fertilizer is 66.558.58 ton CO2, and CO2 emissionfrom transportation for operationalization of plantation company is 16.688,24 ton CO2. Keyword: GHG emission, CO2 absorpsion, plantation Company, transportation, synthetic fertilizer